Sociology for change : the official annual of the Hong Kong Sociological Association - Bian, Yanjie, 1955-; Chan, Kwok B.; Cheung, Tak-sing (Social transformations in Chinese societies, 2006)
Social Transformations in Chinese Societies is the offi cial annual of The Hong Kong Sociological Association. It publishes articles of original research that addresses theoretical, methodological, or substantive issues of sociological significance about social transformations in Chinese societies. The focus is mainly on Hong Kong, Macao, Taiwan, the Mainland, Singapore, and Chinese overseas.